PRL Integrated Library System - Kulkarni, D. R.; Bharucha, R. R. (Journal of Information and Knowledge, 1987)
The paper describes the difficulties encountered in developing a fully integrated library automated system. Alternatively, it suggests, the functional approach of designing subsystems with user friendly interfaces; so that they function as one integrated system. Following this, the subsystems designed at PRL have been briefly described. It is felt that this is the most practical and feasible approach to integration of library systems.